Zambia’s Infrastructure : A Continental Perspective - Foster, Vivien; Dominguez, Carolina (2012)
Infrastructure improvements contributed 0.6 percentage points to Zambia's annual per capital GDP growth over the past decade, mostly because of exponential growth in information and communication services. The power sector, by contrast, pulled the growth rate down by more than 0.1 percentage points. Improving Zambia's infrastructure endowment could boost growth by up to 2 percentage points per year. Zambia's relatively high generation capacity and power consumption are accompanied by fewer power outages than elsewhere in the region. But Zambia's power sector emphasizes the mining industry, while household electrification is about half that in other resource-rich countries. Zambia's power tariffs, among the lowest in Africa, are less than half the level needed to accelerate electrification and keep pace with mining sector demands. In power as in just about every other aspect of infrastructure, rural Zambians lag well behind their African peers. In a country where 70 percent of the population depends on agriculture for its livelihood, this represents a huge drag on the economy. Zambia would need to spend an average of $1.6 billion a year over the decade 2006-15 to develop the infrastructure found in the rest of the developing world. This is equivalent to 20 percent of Zambia's GDP and about double the country's rate of investment in recent years. Closing the country's annual infrastructure funding gap of $500 million requires raising more funds, looking for more cost-effective ways to meet infrastructure targets, and eliminating the inefficiencies that cause the loss of $300 million annually.